2022
DOI: 10.1039/d2dt02406c
|View full text |Cite
|
Sign up to set email alerts
|

Two novel zinc-based MOFs as luminescence sensors to detect phenylglyoxylic acid

Abstract: Automobile exhaust gases, plastic pollutants, smoking, and other harmful substances have been caused serious harm to human beings and the environment. Styrene as a common air poison enters the human...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…As shown in Figure b, there is a good linear relationship between I 0 / I and the PGA concentration ([ M ]) in the range of 0–300 μM ( R 2 = 0.9971), and the calculated K sv was 1.26 × 10 4 M –1 . By the calculation of the 3σ/ K sv formula, the LOD was calculated to be 2.38 μM, which was lower than the critical level of 1.67 × 10 –3 M reported by the American Conference of Governmental Industrial Hygienists (ACGIH) and was even better than that of the previously reported material or method. , The results indicate that 2 can be applied as an efficient disposable sensor detecting PGA, even if the fluorescence detection process is irreversible. During the detection process, the turbid complex suspension becomes clear.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…As shown in Figure b, there is a good linear relationship between I 0 / I and the PGA concentration ([ M ]) in the range of 0–300 μM ( R 2 = 0.9971), and the calculated K sv was 1.26 × 10 4 M –1 . By the calculation of the 3σ/ K sv formula, the LOD was calculated to be 2.38 μM, which was lower than the critical level of 1.67 × 10 –3 M reported by the American Conference of Governmental Industrial Hygienists (ACGIH) and was even better than that of the previously reported material or method. , The results indicate that 2 can be applied as an efficient disposable sensor detecting PGA, even if the fluorescence detection process is irreversible. During the detection process, the turbid complex suspension becomes clear.…”
Section: Resultsmentioning
confidence: 68%
“…Nowadays, the growing concern over chemical pollutants and their impact on ecological security and human health has gained significant attention. , Styrene is an important industrial material for polymers and plays an important role in the manufacturing of plastics and rubber. However, styrene is also a notoriously toxic organic compound. It infiltrates the human body through either inhalation or skin absorption, which is harmful to the nervous system, blood system, and digestive system, and even causes cancer. , Fortunately, styrene can be transformed into phenylglyoxylic acid (PGA) and subsequently be expelled from the body .…”
Section: Introductionmentioning
confidence: 99%
“…19−21 Currently, Ln-CPs have shown good sensing abilities for anions and cations, 22,23 small organic molecules, 24,25 gases, 26,27 and nitro explosives. 28,29 However, in most cases, luminescent sensing involving CPs utilizes suspensions in various solvents 19,23 or test paper strips, 30,31 which often lack the durability, analytical signal stability, or recycling possibility. Therefore, it is important to design a functional and practical luminescent Ln-CP sensor for ATP in urine.…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanide coordination polymers (Ln-CPs), crystalline materials constructed from lanthanide ions or clusters and organic ligands, exhibit excellent luminescent properties due to the ligand “antenna effect” and are widely used in the field of luminescent sensing. Currently, Ln-CPs have shown good sensing abilities for anions and cations, , small organic molecules, , gases, , and nitro explosives. , However, in most cases, luminescent sensing involving CPs utilizes suspensions in various solvents , or test paper strips, , which often lack the durability, analytical signal stability, or recycling possibility. Therefore, it is important to design a functional and practical luminescent Ln-CP sensor for ATP in urine.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc( ii ) and cadmium( ii ) complexes establish one of the most important classes of emissive compounds. 71–121 Earlier, we synthesized a series of mononuclear zinc( ii ) and cadmium( ii ) complexes with hybrid ligands containing a 2,2′-bipyridine moiety and natural terpene (+)-limonene or (+)-3-carene moieties and demonstrated that they exhibit luminescence with the quantum yield increasing in the following order: free ligand < cadmium( ii ) complex < zinc( ii ) complex. 122 The complexes with the limonene derivative demonstrate excitation wavelength–dependent emission with nanosecond and microsecond lifetimes of the excited states.…”
Section: Introductionmentioning
confidence: 99%